Machine learning for medical image reconstruction : second International Workshop, MLMIR 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings /: second International Workshop, MLMIR 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings. (2019) - Unknown
No abstract available